Decreased Readmissions and Improved Quality of Care With the Use of an Inexpensive Checklist in Heart Failure. Issue 4 (1st August 2013) - Basoor, Abhijeet; Doshi, Nitin C.; Cotant, John F.; Saleh, Tarek; Todorov, Mina; Choksi, Nishit; Patel, Kiritkumar C.; DeGregorio, Michele; Mehta, Rajendra H.; Halabi, Abdul R.
Abstract : Providing effective discharge instructions, appropriate dose uptitration, education regarding heart failure (HF) monitoring, and strict follow‐up have all been shown to decrease readmissions for HF but are all underutilized. The authors developed and evaluated the impact of a quality‐improvement HF checklist as a tool to remind physicians to improve quality of care in HF patients. The checklist was used in randomly selected patients admitted with a primary diagnosis of acute decompensated HF. It included documentation regarding medications and dose uptitration, relevant counseling, and follow‐up instructions at discharge. The checklist was used in 48 patients, and this checklist group was compared with 48 patients as a randomly selected control group. Higher proportions of patients were taking angiotensin‐converting enzyme (ACE) inhibitors or angiotensin receptor blockers (ARBs) in the checklist group compared with the control group (40 of 48 vs 23 of 48, P <.001). Compared with the controls, the rate of dose uptitration for β‐blockers and/or ACE inhibitors/ARBs was more common in the checklist group (4 of 48 vs 21 of 48, P <.001). Both 30‐day (19% to 6%) and 6‐month (42% to 23%) readmissions were lower in the checklist group. The use of an HF checklist was associated with better quality of care and decreased readmission rates for patients admitted with HF.